2013
DOI: 10.1523/jneurosci.4216-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

LHX2 Is Necessary for the Maintenance of Optic Identity and for the Progression of Optic Morphogenesis

Abstract: Eye formation is regulated by a complex network of eye field transcription factors (EFTFs) including LIM-homeodomain gene Lhx2. We disrupted Lhx2 function at different stages during this process using a conditional knockout strategy in mice. We find that Lhx2 function is required in an ongoing fashion to maintain optic identity across multiple stages, from the formation of the optic vesicle to the differentiation of the neuroretina. At each stage loss of Lhx2 led to upregulation of a set of molecular markers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 53 publications
5
82
0
Order By: Relevance
“…Lhx2 is the LIM-HD protein co-expressed with Ldb1 in RPCs in early and late stages of retinogenesis, and is required for maintaining the RPCs (Gordon et al, 2013;Roy et al, 2013;Balasubramanian et al, 2014). To examine the physical interaction between Ldb1 and Lhx2, we conducted coimmunoprecipitation with Ldb1 antibodies, with IgG used as control, from wild-type E15.5 eyes and P0 retinas (Fig.…”
Section: ;Ldb2mentioning
confidence: 99%
See 1 more Smart Citation
“…Lhx2 is the LIM-HD protein co-expressed with Ldb1 in RPCs in early and late stages of retinogenesis, and is required for maintaining the RPCs (Gordon et al, 2013;Roy et al, 2013;Balasubramanian et al, 2014). To examine the physical interaction between Ldb1 and Lhx2, we conducted coimmunoprecipitation with Ldb1 antibodies, with IgG used as control, from wild-type E15.5 eyes and P0 retinas (Fig.…”
Section: ;Ldb2mentioning
confidence: 99%
“…Lhx2 is a LIM-HD family member that is expressed in proliferating RPCs (Balasubramanian et al, 2014), and is required for the morphogenesis and patterning of the OV and OC, as well as for maintaining the pool of RPCs (Porter et al, 1997;Yun et al, 2009;Hagglund et al, 2011;Gordon et al, 2013;Roy et al, 2013). Lhx2 expression is also maintained in mature Müller glia, where it controls stress responses (de Melo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We recently observed that selective deletion of Lhx2 in neuroretina after lens placode induction led to severe microphthalmia and a near-total loss of the expression of many retinal progenitor-specific genes (Roy et al, 2013). Interestingly, we also noticed severe disruptions of lens development in these animals.…”
Section: Introductionmentioning
confidence: 67%
“…To identify candidate retinal-derived factors whose expression was altered in Lhx2-deficient neuroretina, we analyzed previously reported microarray data obtained from retinas of control and Chx10-Cre;Lhx2 lox/lox mice at E13.5 (Roy et al, 2013; Accession number GSE87707). These data indicated that multiple different FGFs and FGF-regulated genes showed altered expression in Chx10-Cre;Lhx2 lox/lox retina.…”
Section: Fgf Signaling Is Downregulated In Lhx2-deficient Eyesmentioning
confidence: 99%
See 1 more Smart Citation